2015
DOI: 10.1007/s00586-015-3855-8
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and accuracy of ultrasound measurements with and without the aid of previous radiographs in adolescent idiopathic scoliosis (AIS)

Abstract: Using a previous radiograph as a measurement aid helped the user to measure coronal curvature from US images, and improved the accuracy of end-vertebrae selection. US showed high sensitivity and specificity for detecting curve progression, indicating that US may be a suitable, radiation-free alternative for monitoring patients with AIS who have mild or moderate curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…For ultrasound assessments, the reconstructed 3-D ultrasound images of vertebra were shown in the 3 orthogonal planes (coronal, sagittal and transverse) ( Fig 2 ). The center of laminar (COL) method was applied to measure the spinal curvature angle in the coronal plane [ 15 , 23 , 24 ]. The laminae at each vertebral level were identified manually in the coronal plane of ultrasound image.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For ultrasound assessments, the reconstructed 3-D ultrasound images of vertebra were shown in the 3 orthogonal planes (coronal, sagittal and transverse) ( Fig 2 ). The center of laminar (COL) method was applied to measure the spinal curvature angle in the coronal plane [ 15 , 23 , 24 ]. The laminae at each vertebral level were identified manually in the coronal plane of ultrasound image.…”
Section: Methodsmentioning
confidence: 99%
“…The intra- and inter-reliability of the COL method was showed to be high for the patients with AIS ranged from 12° to 45°. Furthermore, the correlation was found between the COL method in ultrasound and the Cobb method in radiograph [ 23 , 24 ]; the measurement difference between these two methods was less than 5° [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen et al [16,17] validated that upright ultrasound spine images could be obtained and the center of lamina (COL) method using the ultrasound images provided both Cobb angle and AVR measurements. The Cobb angle validation studies were reported [18,19]. The purpose of this study was to determine the intra-and inter-observer reliability of the AVR measurements on both in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has also emerged as a useful, low cost tool for applications that involve imaging bone structures such as guidance for epidural anesthesia (Ashab et al, 2013), bone fracture assessment (Haci-haliloglu et al, 2009) and scoliosis assessment and monitoring (Young et al, 2015;Ungi et al, 2014). However, the interpretation of bone ultrasound images is very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Potential applications include deformity assessment (Ungi et al, 2014;Cheung et al, 2015;Young et al, 2015), spinal brace adjustment Li et al, 2012) and dense 3D spine surface reconstruction (Nguyen et al, 2015). The current gold standard measure for assessing scoliosis (as well as its progression or the effectiveness of a treatment) is the Cobb angle, measured on postero-anterior X-ray images.…”
Section: Introductionmentioning
confidence: 99%